The Tripartite Rhizobacteria-AM Fungal-Host Plant Relationship in Winter Wheat: Impact of Multi-Species Inoculation, Tillage Regime and Naturally Occurring Rhizobacteria Species - Thomas I. Wilkes; Douglas J. Warner; Veronica Edmonds-Brown; Keith G. Davies; Ian Denholm (Plants, 2021)
Soils and plant root rhizospheres have diverse microorganism profiles. Components of this naturally occurring microbiome, arbuscular mycorrhizal (AM) fungi and plant growth promoting rhizobacteria (PGPR), may be beneficial to plant growth. Supplementary application to host plants of AM fungi and PGPR either as single species or multiple species inoculants has the potential to enhance this symbiotic relationship further. Single species interactions have been described; the nature of multi-species tripartite relationships between AM fungi, PGPR and the host plant require further scrutiny. The impact of select Bacilli spp. rhizobacteria and the AM fungus Rhizophagus intraradices as both single and combined inoculations (PGPR[i] and AMF[i]) within field extracted arable soils of two tillage treatments, conventional soil inversion (CT) and zero tillage (ZT) at winter wheat growth stages GS30 and GS39 have been conducted. The naturally occurring soil borne species (PGPR[s] and AMF[s]) have been determined by qPCR analysis. Significant differences (p < 0.05) were evident between inocula treatments and the method of seedbed preparation. A positive impact on wheat plant growth was noted for B. amyloliquefaciens applied as both a single inoculant (PGPR[i]) and in combination with R. intraradices (PGPR[i] + AMF[i]); however, the two treatments did not differ significantly from each other. The findings are discussed in the context of the inocula applied and the naturally occurring soil borne PGPR[s] present in the field extracted soil under each method of tillage.